Delay Factor Analysis and Dynamic System Modeling on the EPC Project of Liquid Petreleum Gas Tank in Kupang - Fachrully Ade, Agung; Santoso, Sugeng (Journal Research of Social Science, Economics, and Management, 2023)
Project delays are an event that often occurs in every project, especially projects with the scope of Engineering Procurement & Construction (EPC) in Indonesia. Many factors affect the slowness of the project so that the performance of a project will not run well if supervision and control are not carried out. The purpose of this study is to find out what are the factors that cause delays, make modeling using dynamic systems and how to make effective managerial suggestions to accelerate project performance. This research method uses mixed methods. The results of this study there are 3 factors that cause delays in the project, starting from the largest factor based on the results of the mean rank analysis is the Construction factor, followed by Procurement, and finally Engineering. In the Construction Factor, five main indicators were taken to cause the delay in the Petreleum Gas Liquid Tank EPC project in Kupang which occurred because the material did not meet specifications, work was stopped due to design changes, delays in project manager decision making, differences of opinion between contractors and consultants, and poor construction quality. Managerial advice in this study is to improve the quality of Human Resources and improve communication networks, tighten the control function and evaluate periodically.